EVALUASI PERAN APARAT PENGAWAS INTERN PEMERINTAH DALAM MANAJEMEN RISIKO PADA INSPEKTORAT KEMENTERIAN X - Sembiring, Hiasinta Florentina; Dyah Setyaningrum (Jurnal Akuntansi Trisakti, 2024)
This study aims to evaluate the role of Government Internal Supervisory Apparatus in risk management at the Inspectorate of Ministry X, in accordance with applicable regulations. This research was conducted at Inspectorate of Ministry X, with a qualitative method through a case study approach. The data collection methods adopted in this study include document analysis, survey, and interviews. The results showed that The Inspectorate of the Ministry of X as Government Internal Supervisory Apparatus has not carried out its core role in implementing Enterprise Risk Management in accordance with the Institute of Internal Auditors Position Paper: The Role of Internal Auditing in Enterprise-Wide Risk Management. Core roles relate to providing objective assurance on the appropriateness and effectiveness of risk management. Other additional roles that may be carried out with adequate consideration have also not been fully implemented such as maintaining and developing the Enterprise Risk Management framework; devepoling risk management strategy for Board approval; and consolidated reporting on risk. While the roles that are not allowed to be carried out in Enterprise Risk Management are not carried out by internal auditors to maintain objectivity and independence when providing assurance services and consulting services. This research is expected to be an input to analyze the role of Government Internal Supervisory Apparatus in risk management at the Ministry of X. For other Government Agencies, this research is expected to be a reference for evaluating the appropriateness of Government Internal Supervisory Apparatus's role in risk management. For academics, the results of this study are expected to be used in subsequent studies to add insight and additional sources of information in conducting further research with a similar theme. This research has not conducted benchmarking with other government agency internal auditors regarding best practices in implementing Government Internal Supervisory Apparatus's role in risk management.